Pengaruh Pemakaian Hair Mask terhadap Hasil Smoothing Rambut Sensitif - Aulia Romadona; Kuswidyaningrum NJ (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to provide learning for hair dressing beginners in performing smoothing treatments on sensitive hair. The technique of using Hair Mask plays an important role in creating the illusion of firm eye folds, thus giving the impression of larger and more expressive eyes. This study uses an experimental method with a quantitative approach involving 4 models with sensitive and damaged hair to be assessed by 16 AKS Ibu Kartini Makeup students. The results of the study showed that the use of Hair Masks on sensitive hair is very necessary to coat the hair pigment before being exposed to smoothing cosmetics. These results can be proven that the success of student practice using Hair Masks is worth (X2) 31% compared to before using Hair Masks (X1) with an average value of 55%. It turns out that this technique is more effective and efficient in increasing success in smoothing because it reduces the risk of hair breakage. (p-value = 0.014). From this study it can be concluded that the use of Hair Masks on smoothing sensitive/damaged hair. This lesson makes a fairly good contribution to AKS Ibu Kartini students to be able to improve skills in smoothing sensitive hair.